Pemikiran dan Gerakan Politik Organisasi Wahdah Islamiyah (WI) di Sulawesi Selatan - Tajuddin, Muhammad Saleh (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2017)
This writing discusses the thought and Political Movements of an Islamic organization, Wahdah Islamiyah (WI), in South Sulawesi. Research type applied is qualitative, and data collection techniques implemented is open interviews. In addition, secondary data collection is carried out by tracking down information through books, internet, journals and other documents. Research findings show that WI comprises a notion of political thought relating to contemporary issues, such as political concepts, tarbiyah, and Islamic law. WI organization has different agendas in its efforts to develop human resources in South Sulawesi. First of all is formal education, and secondly is Islamic sermon. WI organization provides a department dealing specifically with socio political activities and programs. Moreover, the political strategy of WI organization is to collaborate with the government in efforts of enhancing human resources in South Sulawesi.